Evaluating the Usability of the AKUDia Mobile App for Blood Sugar Monitoring: A Feasibility Study - Badriah, Siti; Bahtiar, Yanyan; Setiawan, Henri (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
A variety of ultra-invasive portable blood sugar test kits have been available on the market; these kits require drawing blood from capillaries, which can still be painful and uncomfortable and even enhance the risk of infection. To develop a non-invasive blood sugar meter that is painless and comfortable to use, innovation is required. AKUDia, a mobile application for monitoring blood sugar, was developed as a smart wearable device to help older adults with diabetes stay healthy. This study aimed to measure the usability of the AKUDia application using a usage questionnaire. In terms of a feasibility study, this was quantitative. USE Questionnaire contains a list of questions encompassing 30 questions divided into four dimensions: Usefulness, Ease to use, Ease of learning, and Satisfaction. 50 respondents were recruited for this study, meeting the inclusion criteria of DM patients who had completed a week-long training program on using the AKUDia application. Samples were selected by simple random sampling, and descriptive and univariate data analyses were performed. The AKUDia feasibility test results demonstrated a usability value of 83%, which was classified as very feasible; an ease of use value of 74 percent, which was classified as feasible; an ease of learning value of 83%, which was classified as very feasible; and a satisfaction aspect of 71% at the feasible level. The average usability value of the four categories (usability, ease of use, ease of learning, and satisfaction), which was obtained at 78 percent, indicates that the AKUDia application's usability is at a practicable level. The usability of the AKUDia application is feasible. Governments should support the use and implementation of this innovation in addition to healthcare professionals like doctors and nurses. Information technology systems have the potential to serve as an instrument for illness prevention, treatment, and rehabilitation in addition to promoting health. Future studies should be enhanced to investigate, through experimental research, how the AKUDia application supports nursing care and health management for individuals with diabetes mellitus and the general population.